Small folklore genres as an expression of national character (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In an article in the theme aspect addresses the folklore genres (rhymes, tongue twisters, riddles), characterized by their genre, ritmologiya, lexico-stylistic and grammar covered in them opisanie fragments of national color.
Keywords: folklore; linguostylistic analysis of a text; genre; counting-out rhymes; riddle